(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Climate change is extended an alteration in temperature of normal climate patterns at a particular region. Climate change has been a regular kind of disaster for the agriculture in India. Uttar Pradesh climate is hot monsoon which may consider as warm weather around the year. Climate change has influenced by the major gases of Green House i.e. Co2, Ch4 and N2O and other gasses from fossil fuel burning, motor vehicle pollution. This study is basically focused on at national level, how climate change is affecting to the agriculture production in India that how climate is affecting the agriculture production at national level. In this research secondary data have been used to find out the result. Due to increase in greenhouse gases climate is changing and it is impacting in several ways to the agriculture along with temperature and rainfall. There is a decline in production of Kharif crops and the use of land area due to decrease in rainfall in India. As an extraneous factor fertilizer (N+P+K) play a significant role in sustaining the production of rice and wheat. In concluding remark, it is necessary to take effective measures to stop the climate change as it is impacting on agriculture production negatively in short term but in long term adaptation of climate change will mitigate more than half agriculture production